POLITIK HUKUM PERUNDANG-UNDANGAN TERHADAP ANAK LUAR NIKAH - Muammar Rachman (Qaumiyyah: Jurnal Hukum Tata Negara, 2020)
The formation of the 1974 Marriage Law is based on Islamic Law, which became a problem when the Constitutional Court gave a decision on the judicial review of the Marriage Law with a decision that was considered by the public that the decision was against Islamic law. The research problem in this article is, How is the Politics of Law in the Reform of Legislation in the Post-Constitutional Court Ruling on Marriage related to the status of children outside of marriage? Does the Constitutional Court Decision No 46 / PUU-VII / 2010 contradict Islamic law?The research approach used in this research is normative juridical. The results of the study indicate that children who are born must receive legal protection. If this is not the case, then the children who are born outside of marriage will suffer losses. The relationship between the child and the father does not only occur because of a legal marriage, but can also be based on evidence of a blood relationship between the child and the boy as the father. This is because birth is a legal result of a legal relationship in which there are reciprocal rights and obligations between the child, mother and father. This decision refers, because there is a relationship that is carried out without any legal conditions for marriage, both religiously and in a state, so that it does not cause harm which implies a child who has not done anything wrong. In conclusion, the Constitutional Court granted the renewal of the norm in article 43 of the Marriage Law No. 1 of 1974, which is to provide constitutional rights for children born out of wedlock whether born from a legally valid marriage or not. The decision of the Constitutional Court related to the addition of article 43 paragraph (1) of this marriage law is still in the spirit of Islam as the struggle of Muslims to be able to apply their religious values in this law is not only legally religiously or nationally. Abstrak Pembentukan Undang-Undang (UU) Perkawinan Tahun 1974 berdasarkan Hukum Islam, menjadi permasalahan saat Mahkamah Konstitusi (MK) memutuskan judicial review atas UU perkawinan, bagi masyarakat bertentangan dengan hukum Islam. Permasalahan penelitian ini, Bagaimana Politik Hukum dalam Pembaharuan Peraturan Perundang-Undangan dalam UU Perkawinan Pasca Putusan MK terkait dengan status anak diluar nikah? Apakah Putusan MK No 46/PUU-VII/2010 bertentangan dengan hukum Islam? Pendekatan penelitian ini yuridis normatif. Hasil penelitian menguraikan, anak yang lahir harus mendapat perlindungan hukum. Jika tidak, yang dirugikan adalah anak yang dilahirkan diluar perkawinan. hubungan anak dengan bapak tidak semata-mata terjadi karena adanya sebuah perkawinan yang sah, tapi berdasar pembuktian adanya hubungan darah antara anak dan laki-laki sebagai bapak. Hal ini karena kelahiran adalah akibat hukum dari hubungan hukum yang terdapat hak dan kewajiban secara timbal balik. Putusan ini mengacu, sebab adanya hubungan yang dilakukan tanpa adanya syarat pernikahan yang sah, baik secara agamadan negara, sehingga tidak menimbulkan kerugian yang berimplikasi pada anak yang tidak melakukan kesalahan. Pembaharuan norma dalam pasal 43 UU Perkawinan No. 1 Tahun 1974, memberikan hak konstitusional anak yang dilahirkan di luar nikah baik yang lahir dari pernikahan yang sah secara agama atau tidak. Putusan MK terkait penambahan pasal 43 ayat (1) UU perkawinan masih bernafaskan Islam sesuai perjuangan ummat Islam untuk dapat menjalankan nilai-nilai agamanya dalam UU ini hannya tidak sah secara agama dan Negara.